A baseline record of trace elements concentration along the beach placer mining areas of Kanyakumari coast, South India. Issue 1 (15th June 2017) - Simon Peter, T.; Chandrasekar, N.; John Wilson, J.S.; Selvakumar, S.; Krishnakumar, S.; Magesh, N.S.
Abstract: Trace element concentration in the beach placer mining areas of Kanyakumari coast, South India was assessed. Sewage and contaminated sediments from mining sites has contaminated the surface sediments. Enrichment factor indicates moderately severe enrichment for Pb, minor enrichment for Mn, Zn, Ni, Fe and no enrichment for Cr and Cu. The Igeo values show higher concentration of Pb ranging in the scale of 3–4, which shows strong contamination due to high anthropogenic activity such as mining and terrestrial influences into the coastal regions. Correlation coefficient shows that most of the elements are associated with each other except Ni and Pb. Factor analysis reveals that Mn, Zn, Fe, Cr, Pb and Cu are having a significant loading and it indicates that these elements are mainly derived from similar origin. The cluster analysis clearly indicated that the mining areas are grouped under cluster 2 and non-mining areas are clustered under group 1. Highlights: Trace element content in the beach placer mining areas of Kanyakumari coast has been evaluated. The trace elements are enriched in the sediments of active mining areas. The presence of ilmenite contributes Fe and Mn to the sediments. High Pb concentration is observed in estuarine dominated regions.